2004
DOI: 10.1263/jbb.97.65
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ammonium Addition on Methanogenic Community in a Fluidized Bed Anaerobic Digestion

Abstract: After immobilization of anaerobes on carbon felt in a fluidized-bed anaerobic digester at an ammonium concentration of 500 mg N/l, the results of real-time PCR analysis indicated that the cell densities of the immobilized methanogens and bacteria increased compared with those of the free-living methanogens and bacteria in the original anaerobically digested sewage sludge, respectively. The results of the clone analysis of the original sludge suggested that the major methanogens were Methanosaeta sp. and the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…The aqueous phase contained 45 wt.% of the algae feedstock, much of it organic carbon, but had 19,400 mg/L total nitrogen (TN) and a C/N ratio of 2. Since C/N should be 20 to 30 for successful AD (Fricke et al 2007) and since methanogenic activity ceased at 6,000 mg NH 4 -N/L (Sawayama et al 2004), the nitrogen level is too high for Dun-Dunaliella; Chl-Chlorella; Des-Desmodesmus; Nan-Nannochloropsis; Por-Porphyridium; Sce-Scenedesmus; Spr-Spirulina. By difference after assaying aqueous dissolved solids by evaporation and filtration.…”
Section: Hydrothermal Liquefaction Processmentioning
confidence: 99%
“…The aqueous phase contained 45 wt.% of the algae feedstock, much of it organic carbon, but had 19,400 mg/L total nitrogen (TN) and a C/N ratio of 2. Since C/N should be 20 to 30 for successful AD (Fricke et al 2007) and since methanogenic activity ceased at 6,000 mg NH 4 -N/L (Sawayama et al 2004), the nitrogen level is too high for Dun-Dunaliella; Chl-Chlorella; Des-Desmodesmus; Nan-Nannochloropsis; Por-Porphyridium; Sce-Scenedesmus; Spr-Spirulina. By difference after assaying aqueous dissolved solids by evaporation and filtration.…”
Section: Hydrothermal Liquefaction Processmentioning
confidence: 99%
“…The Methanosarcina sp. was more severely affected by high ammonium concentration than the hydrogen utilizing methanogens (Sawayama et al, 2004). In contrast, a study by Calli et al an abundant number of Methanosarcina-like methanogens at elevated ammonium concentration (6000 mg/l TAN) was observed (Calli et al, 2005b).…”
Section: Influential Parameters On Biomethane Generation In Anaerobicmentioning
confidence: 75%
“…Therefore, as a results of degradation of the organic nitrogen fraction, high concentration of total ammonium (ammonium (NH 4 + ) plus free ammonia (NH 3 ) in these waste/wastewater is common (Jokela & Rintala, 2003). Many studies have shown that free ammonia and not ammonium is responsible to inhibit the methanogenic activity during the anaerobic digestion (Sawayama et al, 2004;Sossa et al, 2004;Calli et al, 2005a;Garcia & Angenent, 2009). In a solution, the ammonia exists in a pH dependent equilibrium between ammonium ion (NH 4 + ) and unionized ammonia or free ammonia (NH 3 ) (see Equation 4).…”
Section: Ammoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Methanoseate와 같은 acetoclastic methanogen은 암모니아의 농도가 약 1.00 g/L 이상으로 높으면 생장이 저해되고, acetate는 syntrophic bacteria에 의해 H2와 CO2 로 분해된다 (Steinhaus et al, 2007;Song et al, 2010). 그때에 암모니아에 대한 민감도가 acetoclastic methanogen보다 낮은 hydrogenotrophic methanogen이 H2와 CO2로부터 메탄을 생성 할 수 있다 (Sawayama et al, 2004). 본 연구의 3단계 메탄생산 공 정의 2차 혐기성 산생성조에서 우점한 Tepidanaerobacter 속은 acetate를 산화하는 syntrophic bacteria로 10.00 g/L 이상의 암모니 아에서도 생장이 가능하고, 2차 공정에서 확인된 hydrogenotrophic methanogen의 Methanoculleus 속과 공생관계를 이루어야 생장이 가능한 세균으로 알려져 있다 (Westerholm et al, 2011 …”
Section: Real-time Pcrunclassified